Enriched spatial analysis of air pollution: Application to the city of Bogotá, Colombia - Jin, Zhexu; Velásquez Angel, Mario Andrés; Mura, Ivan; Franco, Juan Felipe (Frontiers in Environmental Science, 2022)
Air pollution is a global health issue, which especially affects people living in highly urbanized areas. Many large cities in the developing world are highly heterogeneous in population density and socioeconomic conditions. Under these circumstances, relying on classical air quality indexes may not be sufficient to provide a detailed view of the impact of air pollution. In the paper, we propose an enriched spatial analysis of air pollution. By performing spatial temporal Kriging on PM2.5 concentration, we obtain a detailed map of its spatial distribution. Then, we integrate the population and socioeconomic features to produce a measure of the inequality between different demographic groups. We consider as a working case the city of Bogota, where demographic features are heterogeneous across different districts. The results of our analyses identify a highly polluted cluster located in the south-west cluster of the city. Within this cluster, we observe a disproportionate representation with people from several vulnerable groups. Overall, our analysis points out significant inequities with regard to the exposure to poor air quality. The analysis we conduct for the city of Bogota is perfectly repeatable on any urban area equipped with an air quality monitoring network.